Pemanfaatan Bunga Rosella dalam Meningkatkan Pendapatan Masyarakat di Kelurahan Ngipik, Kabupaten Gresik - Handayani, Sri Linda; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
Rosella flowers are believed to have quite high health benefits and have a unique taste. In variousstudies, rosella flowers can cure various diseases and prevent various disease transmissions and canbe used as a natural coloring and preservative in food or drinks. This service activity has beencarried out using training and outreach methods, and selling beverage products made from rosellaflowers in the form of tea in bottles. By delivering material about the potential use of rosella flowers,various processed rosella products, and the activities that have been carried out, it is useful toincrease the knowledge and skills of the community, especially PKK women in Ngipik Village, GresikDistrict, Gresik Regency as a form of increasing the income of the people of Ngipik Village, Gresik.Keywords: Benefits; Rosella Flowers; Income